REDESAIN MEJA KERJA GURU SECARA ERGONOMIS DENGAN METODE QFD-NPD PADA JAKARTA INTERCULTURAL SCHOOL AQUATICS - sarwoko sarwoko; Setiyo Puji Muswantoro (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
The word desk used at the Jakarta Intercultural Schol Aquatic were found to be ergonomically inadequate, resulting in reduced comfort during teaching activities. A questionnaire survey involving 41 teachers revealed that all respondents considered the existing desks uncomfortable. The most frequently reported musculoskeletal complaints were lower back pain (68%), leg discomfort (54%), and hand discomfort (29%). This study aimed to redesign the teachers' work desk using an integrated Quality Function Deployment (QFD) and New Product Development (NPD) approach supported by anthropometric data. QFD was employed to identify and prioritize user requirements through the House of Quality (HoQ), while NPD was applied to the stages of concept development, product specification, and prototype design based on the prioritized customer needs. The results indicated that the highest-priority requirements included a wider work surface, a drawer, a bag storage compartment, a stationery holder, and an easily accessible electrical outlet. Anthropometric analysis produced the main desk dimensions of 74 cm in height, 80 cm in length, and 60.31cm in width. The proposed ergonomic desk design is expected to improve teachers' comfort, reduce the risk of musculoskeletal disorders, and serve as a practical reference for developing ergonomic workplace facilities in educational institutions